Autonomous Motivation for Exercise Is Key to an Active Lifestyle in Firefighters. (May 2023) - Vancampfort, Davy; De Soir, Erik; Ramos-Sanchez, Carlos Pelayo; van Winkel, Ruud; Louw, Quinette Abegail; McKeon, Grace; Rosenbaum, Simon; Seedat, Soraya
Background: Physical inactivity is an important risk factor for chronic mental and physical health conditions in firefighters. It remains unclear why a substantial portion of firefighters do not meet the World Health Organization's physical activity (PA) recommendations. In this cross-sectional study, we explored associations between motivational reasons for being physically active and time spent exercising, walking, and in incidental PA in firefighters. A secondary aim was to investigate differences in motivational reasons between physically active versus physically inactive firefighters. Methods: Eighty-seven participants (43.1 ± 10.3 years; 87.6% male) who were recruited via a nonprofit peer support network of fire rescue personnel in Flanders, Belgium, completed the Behavioral Regulation in Exercise Questionnaire 2 (BREQ-2), Simple Physical Activity Questionnaire (SIMPAQ), and the Physical Activity Vital Sign (PAVS) via an online survey. Findings: Firefighters who identified the benefits of exercising and/or those who found pleasure or a personal challenge in it exercised more. Those who did not meet the guideline of 150 min of moderate-to-vigorous physical activity per week had much less intrinsic motivation. Conclusions/Implications for Practice: This study demonstrates that autonomous motives for PA (i.e., because it is perceived to be consistent with intrinsic goals or outcomes and emanates from the self) are important for an active lifestyle in firefighters. Occupational health professionals can foster autonomous motivation in firefighters by focusing on the benefits of exercise, making sure there are a wide range of exercise options available, and supporting initiatives of firefighters within the fire station.